PENGARUH AFIRMASI POSITIF TERHADAP KUALITAS TIDUR PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RS MARDIRAHAYU KUDUS - Putri, Devi Setya; Listyarini, Anita Dyah; Mulyani, Tri Dwi (STIKES Cendekia Utama Kudus, 2024)
Patients with chronic kidney failure must undergo hemodialysis therapy to extend life expectancy. Kidney failure sufferers experience physical, psychological and social disorders. The physical problem that sufferers often experience as a result of the disease is decreased sleep quality. Poor sleep quality results in decreased quality of life, risk of accidents, malaise, fatigue, increased risk of falls and cognitive decline. Actions to improve sleep quality by using positive affirmations. This study aims to determine the effect of positive affirmations on the sleep quality of chronic kidney failure patients undergoing hemodialysis at Mardi Rahayu Kudus Hospital. Quasy Experiment research type with One Group Pre test and post test design. Population of Chronic Kidney Failure sufferers undergoing hemodialysis. The sampling technique was purposive sampling so the sample size was 38 respondents. Data analysis using the Wilcoxon test. The result got of sleep quality before the procedure was all poor (100%) and after the procedure was 21.1% good and 78.9% poor. Wilcoxon analysis obtained a p value of 0.000. There is a significant effect of positive affirmations on the sleep quality of chronic kidney failure patients undergoing hemodialysis at Mardi Rahayu Kudus Hospital. It is recommended that nurses apply positive affirmative actions to improve the sleep quality of kidney failure patients undergoing hemodialysis. Keywords: Positive Affirmations, Sleep Quality, Hemodialysis.